Effect of core size on the magnetoelectric properties of Cu0.8Co0.2Fe2O4@Ba0.8Sr0.2TiO3 ceramics. (January 2022) - Wu, Heng; Xu, Ruicheng; Zhou, Chuang; Xing, Shulin; Zeng, Zhixin; Ao, Hong; Li, Wenchuan; Qin, Xiaofeng; Gao, Rongli
Abstract: Cu0.8 Co0.2 Fe2 O4 @Ba0.8 Sr0.2 TiO3 ceramics (@ stands for core-shell structure) were prepared by the sol-gel method, and the effects of the core size (20 nm, 40 nm, 50 nm, and 70 nm) on the microstructure, electrical properties, magnetic properties, and magnetoelectric coupling were studied. X-ray diffraction patterns show that Cu0.8 Co0.2 Fe2 O4 @Ba0.8 Sr0.2 TiO3 ceramics have a biphasic structure and only a small amount of Ba3 Fe32 O51 impurity phase exists when the core size is 70 nm. Scanning electron microscopy shows that the surface of all samples is relatively uniform except for a few holes and agglomerations. Transmission electron microscopy revealed an obvious shell-core structure, but the cladding effect became worse as the core size increased. The dielectric constant increases and the dielectric loss decreases with increase of the core size. However, as the core size increases, the change in the dielectric constant of the ceramic samples decreases with application of an external magnetic field. As the core size increases, the ferroelectric properties of the samples are gradually improved, and the ferroelectric properties are relatively good when the core size is 70 nm. The saturation magnetization ( M s ), remanent magnetization ( M r ), and coercive force ( H c ) of the ceramics decrease with increase of the core size. As the core size increases, the magnetic domain switches more easily. The sample with a core size of 70 nm has strong magnetism, and its magnetoelectric coupling coefficient is about 78.14 V/cm·Oe. Highlights: Core-shell structure Cu0.8 Co0.2 Fe2 O4 @Ba0.8 Sr0.2 TiO3 composite ceramics with different core sizes were prepared by the sol-gel method With increase of the core size, the dielectric constant increases, the dielectric loss decreases, and the dielectric properties of the ceramic with a core size of 70 nm are relatively good. The core is small and the coating effect is good, so the interface effect is strong and the dielectric properties are optimized. This conclusion is verified by the magnetoelectric coupling coefficient. With increase of the core size, M s, M r, and H c decrease. Magnetism comes mainly from Cu0.8 Co0.2 Fe2 O4 . As the core size increases, the magnetic domain is more prone to flipping, so H c decreases. With increase of the core size, the ferroelectric properties of the ceramics are gradually improved, and the ceramic with a core size of 70 nm has relatively good ferroelectric properties.